The Evaluation of Serum Biomarkers for Non-small Cell Lung Cancer (NSCLC) Diagnosis - Fang, Rui; Zhu, Yong; Khadka, Vedbar S.; Zhang, Fan; Jiang, Bin; Deng, Youping (Frontiers in Physiology, 2018)
Abstract Introduction Lung cancer ranks top in the cause of cancer death globally. The identification of effective biomarkers is essential for non-small cell lung cancer (NSCLC) diagnosis. Methods The expression levels of prolactin (PRL), CEA and CYFR21 in serum were assayed by ELISA. The blood samples were attained from 44 NSCLC cases and 44 healthy controls. Logistic regression and receiver operating characteristic (ROC) analyses were applied to evaluate the diagnostic efficacy and create diagnostic mathematical models. Results Serum PRL, CEA and CYFR21 levels were significantly higher in patients with NSCLC than the healthy controls (all P-values <0.001). According to the model to predict NSCLC patients from the healthy controls, a combination of PRL, CEA and CYFR21 biomarkers was more effective than individual biomarker alone, with AUC=0.960 (95% CI: 0.921 to 0.999), sensitivity=0.909, specificity=0.955, positive predicted value=0.952 and negative predicted value=0.913. Conclusion PRL can be used as a potential serum biomarker for the diagnosis of NSCLC. A panel of PRL, CEA and CYFRA21 was found as promising serum biomarkers for the diagnosis of NSCLC with relatively high sensitivity and specificity.